Analysis of the Use of Mobile-Based Aceh Culinary Menu Applications to Improve Customer Experience in the Culinary Industry - Azzahra, Putri latiffa; Yusmaneli; Fathurrahmad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This research analyzes the implementation of mobile-based menu applications for Acehnese cuisine and their impact on enhancing customer experience in the culinary industry. The study examines information technology applications, particularly mobile applications, as tools for improving accessibility and convenience in ordering and obtaining information about Acehnese culinary dishes. The research methodology includes surveys of active users of mobile-based menu applications in the Acehnese culinary industry, focusing on their perceptions of user experience, application effectiveness in presenting information, and impact on customer satisfaction. Case studies were conducted to examine successful implementations of mobile-based menu applications in Acehnese culinary settings. Data analysis provides understanding about the potential of mobile-based menu applications as tools for improving service quality and customer experience in the Acehnese culinary industry. Research findings benefit culinary industry stakeholders and information technology developers in optimizing mobile application utilization to enhance service quality and customer satisfaction